Robust affine maneuver formation control based of second-order multi-agent grid inspection systems - Zhang, Peng; Ma, Dengjun; Liu, Peng; Li, Mengwei (Frontiers in Energy Research, 2022)
Grid formation inspection is the future development trend of grid inspection. Aim to the robust control problem of multi-agent grid inspection system in complex environment, this paper proposes a formation control algorithm with prescribed performance. The dynamic model of follower distance error is given in the leader-follower framework using a symbolic Laplace matrix. Performance bounds are set on the sliding mode error by prescribed performance control. Then, the convergence and stability of the proposed control algorithm are not only proved by the Lyapunov stability theorem, but also the error state of the system converges to the prescribed performance bound. Finally, the simulation results show that the follower can follow the leader despite external interference and the validity of the proposed algorithm.